Heat transformation based on CaCl2/H2O – Part A: Closed operation principle. (5th June 2016) - Richter, Margarethe; Bouché, Martin; Linder, Marc
Highlights: Upgrade and storage of thermal energy using a thermochemical system is investigated. Calcium chloride is used as reference material. Thermal charging at 130 °C, discharging at 165 °C experimentally demonstrated. Limitations and changes during reaction are analyzed. An innovative process concept for thermochemical heat storage is suggested. Abstract: Thermochemical systems based on gas–solid-reactions enable both storage of thermal energy and its thermal upgrade by heat transformation. Thus, they are an interesting and promising option in order to reutilize industrial waste heat and reduce primary energy consumption. In this publication an experimental analysis of the reaction system calcium chloride and water vapor is presented. The endothermic dehydration reaction is used in order to charge the storage at 130 °C while the reverse reaction leads to a discharging at 165 °C. Thus, a thermal upgrade by 35 K could be demonstrated and main limitations by heat and mass transfer were analyzed. Whereas this part focusses on a closed operation principle, the associated part B deals with the open operation utilizing air as purge gas.